Santa Shark a Great white Christmas - Lowery, Mike (New York Orchard Books, an imprint of Scholastic Inc., 2023)
Edgar the shark is getting the house ready for a visit from Santa Shark, and although he is skeptical, his friend Lotta the crab pitches in to help--but Edgar is worried about the lack of snow under the sea.
Ages 4-8.
Grades K-1.
112984
Keywords: Santa Claus -- (Fictitious character) -- Juvenile fiction; Christmas stories; Humorous stories; Sharks -- Juvenile fiction; Crabs -- Juvenile fiction; Christmas -- Fiction; Christmas stories; Juvenile fiction -- Holidays & Celebrations -- Christmas & Advent; Juvenile fiction -- Humorous Stories; Marine animals -- Juvenile fiction; Picture books; Animal fiction; Christmas fiction; Fiction; Humorous fiction; Juvenile works